Political Law in Enforcement Law in Indonesia - Ismidar Ismidar; Tamauina Br. Sembiring; Sri Utami (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Law is a guideline and rules related to the concept of living in society and will always be in accordance with the conditions of society. Law is a demand to be able to provide justice, meaning that law is always faced with the question of whether law can realize justice. Related to the concept of law, legal politics is interpreted as an activity that determines the pattern and method of forming law, supervising the operation of law, and updating law for the purpose of the State. Therefore, law is a determinant of politics, and is also related to democracy in the sense that political activities are regulated and must be subject to legal rules. Law is viewed from the perspective of das sollen (necessity), viewing that law must be guided by relations between members of society. While those who view it from the perspective of das sein (reality), empiricists see that law is greatly influenced by politics not only in the process of making it, but also in its empirical realities. So that law is influenced by politics and even now legal autonomy in Indonesia is often intervened by politics, not only in terms of its making, but also in its application, both in terms of law enforcement. This study aims to determine the impact of the development of legal politics in the law enforcement system in Indonesia and the existence of legal politics in the law enforcement system in Indonesia. The method used in the study is normative juridical.